2017
DOI: 10.1051/matecconf/201712002007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the effect of limestone grading on some mechanical properties of concrete

Abstract: Abstract. This study reports the experimental work undertaken to investigate the optimum grading of limestone to be used in concrete mixes. 36 concrete cubes were prepared for testing. Four different Fineness Moduli and grading were tested 2.4, 2.6, 2.92 and 3. For all tests, the cubes were left in curing until testing at the age of 3, 7 and 28 days respectively. Samples were loaded to failure and the average compressive strength was used for comparison purposes. Flow table test has been performed on the fresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Thomas (2007) [11] also reported that a 10% fly ash addition should result in at least a 3% reduction in the water demand of a cementitious mix, however, the exact value of water reduction depends on the quality of the fly ash. Finally, similarly to fly ash, limestone has been shown to improve the workability of cementitious mixtures through a surface interaction with water and because of this phenomenon, the fineness of the limestone particles has been found to be key in the workability of limestone-OPC blends [32].…”
Section: Introductionmentioning
confidence: 99%
“…Thomas (2007) [11] also reported that a 10% fly ash addition should result in at least a 3% reduction in the water demand of a cementitious mix, however, the exact value of water reduction depends on the quality of the fly ash. Finally, similarly to fly ash, limestone has been shown to improve the workability of cementitious mixtures through a surface interaction with water and because of this phenomenon, the fineness of the limestone particles has been found to be key in the workability of limestone-OPC blends [32].…”
Section: Introductionmentioning
confidence: 99%